2010
DOI: 10.1074/jbc.c110.165076
|View full text |Cite
|
Sign up to set email alerts
|

Only One ATP-binding DnaX Subunit Is Required for Initiation Complex Formation by the Escherichia coli DNA Polymerase III Holoenzyme

Abstract: The DnaX complex (DnaX 3 ␦␦) within the Escherichia coli DNA polymerase III holoenzyme serves to load the dimeric sliding clamp processivity factor, ␤ 2 , onto DNA. The complex contains three DnaX subunits, which occur in two forms: and the shorter ␥, produced by translational frameshifting. Ten forms of E. coli DnaX complex containing all possible combinations of wild-type or a Walker A motif K51E variant or ␥ have been reconstituted and rigorously purified. DnaX complexes containing three DnaX K51E subunits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
(27 reference statements)
3
12
0
Order By: Relevance
“…Because Rfc5 (E site) lacks a trans-acting Arg finger and contains mutations in the Walker B motif that are key for hydrolysis, this mutant was not investigated. Our study extends previous work measuring the effects of Walker A mutations on clamp loading and DNA synthesis in vitro and in vivo (11,12,14,15,43,44) by analyzing the effect of single site Walker A mutations on individual interactions and steps in the clamp loading reaction cycle.…”
Section: Discussionsupporting
confidence: 65%
“…Because Rfc5 (E site) lacks a trans-acting Arg finger and contains mutations in the Walker B motif that are key for hydrolysis, this mutant was not investigated. Our study extends previous work measuring the effects of Walker A mutations on clamp loading and DNA synthesis in vitro and in vivo (11,12,14,15,43,44) by analyzing the effect of single site Walker A mutations on individual interactions and steps in the clamp loading reaction cycle.…”
Section: Discussionsupporting
confidence: 65%
“…DnaX complexes containing a mixture of inactive and wildtype DnaX subunits can function on long single-stranded templates in 5-min reactions (26). Examination of the kinetics of initiation complex formation reveals a 3500-fold lower rate for DnaX complexes containing a single inactive ATPase subunit (39).…”
Section: Discussionmentioning
confidence: 99%
“…The mutation occurs within the Walker A motif and abolishes ATP binding (26). In the presence of Pol III* containing mutant ␥, the total level of rolling circle DNA synthesis is decreased 7-fold (Fig.…”
Section: Dnax Complex With One Inactive Atpase Is Not Competent For Rmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent structural study with the T4 bacteriophage clamp loader suggested that hydrolysis of one ATP molecule causes a conformational change in the clamp loader⅐clamp complex that closes the clamp (30), and studies with the E. coli replisome suggest that hydrolysis of one ATP molecule is sufficient to form initiation complexes but hydrolysis of 3 molecules accelerates the process (31,32). Studies have shown that ATP hydrolysis is required for clamp release (24,26,33), but the question here is whether ATP hydrolysis is required for clamp closing or whether binding of the clamp loader⅐clamp complex to DNA is sufficient to promote clamp closing.…”
mentioning
confidence: 99%